A bibliometric analysis of hotpots and trends for the relationship between skin inflammation and regeneration - Liu, Zhen-jiang; Wang, Mei-juan; Luo, Jia; Tan, Ya-ting; Hou, Min; Wang, Shu-chao (Frontiers in Surgery, 2023)
Skin regeneration is a worldwide difficult problem. More and more research uncovered a remarkable healing role provided by immune cells and the underlying regulatory mechanism. In this research, by using bibliometric analysis, we provided a comprehensive overview of the relationship between skin regeneration and inflammation. Also, we summarized the number of publications, citation frequency, and centrality to analyze current research hotpots and further directions. Last, we reviewed the advanced research results, technology and treatment for skin regeneration. Through this research, it would help new coming researchers to select the research direction and provide a basic knowledge and understanding of current research. Furthermore, it could provide underlying guidelines for the basic research and precise clinical strategies for skin regeneration.